Impact of n-Doping Mechanisms on the Molecular Packing and Electron Mobilities of Molecular Semiconductors for Organic Thermoelectrics - Zeng, Yan; Han, Guangchao; Yi, Yuanping (Organic Materials, 2022)
Electrical conductivity is one of the key parameters for organic thermoelectrics and depends on both the concentration and mobility of charge carriers. To increase the carrier concentration, molecular dopants have to be added into organic semiconductor materials, whereas the introduction of dopants can influence the molecular packing structures and hence carrier mobility of the organic semiconductors. Herein, we have theoretically investigated the impact of different n-doping mechanisms on molecular packing and electron transport properties by taking (4-(1,3-dimethyl-2,3-dihydro-1H-benzoimidazol-2-yl)phenyl)dimethylamine (N-DMBI-H) and quinoid-dicyanomethylene-dipyrrolo-[3,4-c]pyrrole-1,4-diylidene)bis(thieno[3,2-b]thiophene (Q-DCM-DPPTT) respectively as representative n-dopant and molecular semiconductor. The results show that when the doping reactions and charge transfer spontaneously occur in the solution at room temperature, the oppositely charged dopant and semiconductor molecules will be tightly bound to disrupt the semiconductor to form long-range molecular packing, leading to a substantial decrease of electron mobility in the doped film. In contrast, when the doping reactions and charge transfer are activated by heating the doped film, the molecular packing of the semiconductor is slightly affected and hence the electron mobility remains quite high. This work indicates that thermally activated n-doping is an effective way to achieve both high carrier concentration and high electron mobility in n-type organic thermoelectric materials.
Keywords: organic thermoelectric; n-doping mechanisms; molecular packing structure; charge-transport properties